Evolving E-Business: Trends and Strategies for Digital Transformation in the Digital Age - Latief, Fitriani; Firman, Ahmad (Magister Manajemen Universitas Yapis Papua, 2023)
The main objective of this research is to explore how digital transformation, including mobile commerce, social media integration, and Industry 4.0 technologies, influences e-business strategies. By examining the evolving landscape of online commerce, the study aims to identify the strategic imperatives for businesses seeking to thrive in the digital marketplace. This study employs a systematic literature review approach to synthesize and analyze existing research on e-business trends and digital transformation. The research aims to provide a comprehensive overview of the subject matter and extract valuable insights for practitioners and scholars alike by reviewing a diverse range of scholarly articles, reports, and case studies. The findings of this research highlight the transformative impact of digital transformation on e-business strategies. Mobile commerce, social media integration, and Industry 4.0 technologies emerge as significant drivers of change, offering businesses opportunities to enhance customer experiences, drive innovation, and gain competitive advantage. However, successfully implementing digital transformation initiatives requires businesses to address infrastructure, talent, and data governance challenges effectively. This research contributes to the existing body of knowledge by providing valuable insights into the dynamics of e-business strategies in the digital age. By synthesizing key trends, challenges, and opportunities, the study offers practical implications for businesses seeking to navigate the complexities of digital transformation. Additionally, the research underscores the importance of strategic adaptation and agility in responding to disruptive market forces and driving innovation in the digital economy.